Effects of access to primary healthcare services on health vulnerability among older adults in China: focusing on demographic differences - Zhu, Ningli; Li, Jun; Liu, Xiaohui; Luo, Lei; Cheng, Wenwen; Li, Xiaoyu; Yu, Chen; Zhang, Siyu; Zhu, Liang (Frontiers in Public Health, 2025)
BackgroundAgainst the backdrop of an aging population, older adults are confronted with multifaceted challenges, including physiological decline, uneven distribution of medical resources, and economic constraints, which collectively exacerbate their health vulnerability. This study aims to examine the impact of primary healthcare accessibility on health vulnerability among older adults and to explore disparities in access to primary care services across different demographic groups, thereby providing an empirical foundation for promoting healthy aging.MethodsAn online survey was conducted among 398 older adults in China to assess health vulnerability and accessibility to village clinics and township health centers. A baseline model and a multi-group structural equation model were used to analyze the effect of primary healthcare accessibility on health vulnerability.ResultsWhile overall health vulnerability among older adults remained relatively high, accessibility to primary healthcare services was generally favorable. Compared to village clinics, township health centers have significantly higher accessibility. Furthermore, demographic variables such as gender, education level, and marital status demonstrated heterogeneous effects within this relationship.ConclusionPolicy efforts should prioritize enhancing resource allocation and service capacity at the village clinic level. Concurrently, greater attention should be devoted to ensuring healthcare equity for vulnerable subgroups, including women, those living alone, and individuals with lower educational attainment, within the primary healthcare system. These measures will contribute to reducing health vulnerability among older adults and advancing the goal of healthy aging.